Detanning of Deoiled Sal (Shorea robust A) Seed Meal with Sodium Carbonate Followed by Washing with Water - Sanjiva Rao, Y.; Madhusudhan Rao, K. (Indian Forester, 1986)
Detanning of deoiled sal seed meal (DSSM) is studied with sodium carbonate solutions having concentretions of 0.01, 0.015 and 0.02 kg/1., as well as under different to cake ratios of about 34 to 70 1/kg about 78 to 90 percent in DSSM, can be extracted resulting in overall reduction of tannin content to below 4 per cent frorn original tannin content of 123 per cent.